Integration durch Geschichte? (Brill, 2025)
Part of the integration courses offered by the Federal Office for Migration and Refugees (BAMF) is known as an ‘orientation course’, which provides refugees and immigrants with essential knowledge about the state, society and, above all, the history of Germany. This course also conveys social, historical and cultural values and norms. Religious plurality and tolerance towards Jews and Judaism, the memory of the Holocaust, the condemnation of anti-Semitism and the special responsibility towards Israel are implicitly and explicitly covered by the curriculum. This volume brings together analyses of the textbooks and materials used for such courses as well as preliminary reports based on semi-structured interviews and lesson observations, which provide an insight into teaching strategies and course proceedings. The primary focus of this volume is on the challenges and opportunities associated with the way German history covering the period 1933 to 1945 is taught.